Islamic temperature methods of soul interruption (mental health symptoms) - Rahman, Zaizul Ab; Aziz, Abdul; Hallaq, Wael; Abdul Kadir, Fakhrul Adabi; Paad, Nur Shahidah (IAEME Publication, 2018)
God's Word s.w.t: He (Allah) has sent to the ummi (illiterate) a messenger among them; he will recite to them his verses, he will purify them, he will teach them the Qur'an and wisdom. And verily they were before in manifest error. (Al-Jumu'ah 62: 2).The above verse contains the methods of Islamic therapy that every Muslim can use to avoid being illiterate, unable to write or read. Because they do not follow the teachings of Islam, they are so easy to be depressed and disappointed when faced with various trials in the course of travel from world life to the hereafter. They have no clue about ways to develop the personality, the way of life, the way of deeds, and the way of speaking based on Islamic teachings.